Hubungan Komitmen Organisasi Dengan Organizational Citizenship Behavior Pada Perawat - Yanti, Saskia; Qowi, Nurul Hikmatul; Ubudiyah, Masunatul (Jurnal Keperawatan Florence Nightingale, 2025)
Organizational Citizenship Behavior (OCB) refers to voluntary behaviors that exceed formal job requirements and play an important role in enhancing the effectiveness of hospital services. Organizational commitment is believed to be one of the factors influencing the emergence of OCB. This study aimed to examine the relationship between organizational commitment and OCB among nurses at Hospital. This research employed a cross-sectional design. The sample consisted of 85 nurses selected using total sampling. Data were collected using organizational commitment and OCB questionnaires. The results showed that most nurses (63.5%) had high organizational commitment, and nearly most of them (61.2%) exhibited high OCB. Statistical analysis using the Spearman Rho test revealed a p-value of 0.000 (p < 0.05) and a correlation coefficient (rₛ) of 0.975. Therefore, the alternative hypothesis (H₁) was accepted, indicating a significant relationship between organizational commitment and OCB among nurses at Hospital. Based on these findings, it is recommended that the hospital maintain consistency in reinforcing organizational values, encourage active managerial involvement, and conduct regular evaluations of nurses’ work behaviors to enhance their OCB.